Cross sections for the formation of 114mIn and 116mIn on bombardment of cadmium by deuterons - Nassiff, S. J.; Usher, O. Herreros; Wasilevsky, C. (Elsevier B.V., 1979)
Fil: Nassiff, S. J. Comisión Nacional de Energía Atómica; Argentina